Relationship between poverty and inequality: a case study of Bumiputera household in the Northern States of Malaysia - Bahari, Zakaria; Mohd, Saidatulakmal; Hamat, Abdul Fatah Che (2015)

(untitled)
The relationship between poverty and inequality has never been straightforward. While some research found that poverty does not mirror inequality, others found that a change in income inequality definitely affects poverty. Malaysia has been applauded by international organizations for its success in alleviating poverty. However, inequality as measured by Gini coefficient has only shown a marginal drop from 0.46 in 1992 to 0.43 in 2012. This situation is more apparent when inequality is assessed according to ethnic groups. While the ethnic inequality measure has narrowed, the inequality for the Bumiputeras remains high. The Gini coefficient of the Bumiputeras stands at 0.42 in 2012, a drop of 0.02 from 1992. The Bumiputera, which is literally known as the ‘son of the soil’ is the largest ethnic group in Malaysia. In 2012, there is only 2.2 per cent Bumiputeras living in absolute poverty. This seems a small percentage but pockets of poverty among Bumiputeras remain. At present, there is a lack of research in understanding the relationship between poverty and inequality among the Bumiputeras, particularly in the Northern States of Malaysia. This study assesses the relationship between poverty and inequality of the Bumiputera Household in the Northern States of Malaysia using the Household Income Survey (HIS) data for 2009. A logistic probability function with values of 1 and 0 to represent households living in poverty and household not living in poverty respectively, is employed. Contextual inequality as measured by Theil Index is used as a proxy to inequality. The analysis found that per capita income and education attainment (except for tertiary education) significantly affect poverty. The study found no significant relationship exists between poverty and inequality. This provides an important implication towards policy formulation. Policy to tackle the issues of poverty and inequality need to be addressed separately, rather than pursued simultaneously.